2001
DOI: 10.1074/jbc.m105260200
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Complexes of the FERM Domain-containing Protein GRSP1 Bound to ARF Exchange Factor GRP1

Abstract: GRP1 is a member of a family of proteins that contain a coiled-coil region, a Sec7 homology domain with guanosine nucleotide exchange activity for the ARF GTP-binding proteins, and a pleckstrin homology domain at the C terminus. The pleckstrin homology domain of GRP1 binds phosphatidylinositol (3,4,5) trisphosphate and mediates the translocation of GRP1 to the plasma membrane upon agonist stimulation of PI 3-kinase activity. Using a 32 P-labeled GRP1 probe to screen a mouse brain cDNA expression library, we is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 33 publications
2
53
0
2
Order By: Relevance
“…GRSP-1 has been reported to bind to Grp-1 and colocalize with F-actin in membrane ruffles upon stimulation with insulin in CHO-T cells (22). The GFP-tagged GRSP-1 localized together with Par-3 at spot-like AJs and TJs in EpH4 cells and at AJs in NIH 3T3 cells (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…GRSP-1 has been reported to bind to Grp-1 and colocalize with F-actin in membrane ruffles upon stimulation with insulin in CHO-T cells (22). The GFP-tagged GRSP-1 localized together with Par-3 at spot-like AJs and TJs in EpH4 cells and at AJs in NIH 3T3 cells (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…In addition to IPCEF1, the cytohesins have been found to interact with various other scaffold proteins, including GRASP/tamalin (Nevrivy et al 2000;Kitano et al 2002), CASP/Cybr/CYTIP (Mansour et al 2002;Tang et al 2002), and GRSP1 (Klarlund et al 2001). Although there is no primary sequence in common among these scaffolds, binding is mediated by the N-terminal coiled-coil (CC) domain present in the cytohesins and regions in each scaffold that also possess CC structure.…”
Section: Resultsmentioning
confidence: 99%
“…IPCEF interacts with both ARNO and GRP1 by two-hybrid assay, although only the interaction with ARNO was confirmed with recombinant proteins (37). GRSP1 interacts with GRP1, and it is not known whether this protein can also bind to ARNO (38). It has been shown that these proteins co-localize with cytohesins and modify their ARF6-activating activity (37).…”
Section: Discussionmentioning
confidence: 99%